2015
DOI: 10.1590/0103-5150.028.001.ao09
|View full text |Cite
|
Sign up to set email alerts
|

Healthy preterm infants: global motor coordination and early intervention

Abstract: Introduction Studies recommend a participation by preterm children (PT) in Early Intervention Programs (EIP), as the coordination dysfunctions appear to occur more frequently in premature school children. Objectives Describe the global motor coordination (MC) in PT children that participate in an EIP; verify the difference in MC between the sexes and correlate the coordination results of PT children and those with gestation age (GA) and the birth weight (BW); and compare the results of MC between PT children a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
1
3
0
1
Order By: Relevance
“…In a study of premature and full-term newborns, the authors found that the premature children mastered overall motor coordination, suggesting that the intervention program used facilitated their development (24). This result corroborates the indings of the present study, where the average score in the TG was normal, while children in the PG scored mainly between medium normal and very high when analyzed separately, due to the combination of early intervention and external factors.…”
Section: Discussionsupporting
confidence: 90%
“…In a study of premature and full-term newborns, the authors found that the premature children mastered overall motor coordination, suggesting that the intervention program used facilitated their development (24). This result corroborates the indings of the present study, where the average score in the TG was normal, while children in the PG scored mainly between medium normal and very high when analyzed separately, due to the combination of early intervention and external factors.…”
Section: Discussionsupporting
confidence: 90%
“…The authors assessed 37 children aged between 5 and 6 years with a mean GA of 33.54 weeks in the preterm group. In both the abovementioned studies, the preterm children were within the normal spectrum according to the instruments used and showed no difference in gross motor skills when compared to children born fullterm (37,38). As in the present study, a possible explanation for the difference found in relation to the literature may be the higher mean GA and birth weight (BW) when compared to other studies, which evaluated children with a GA of under 33 weeks and weight less than 1,500 g. These results reinforce the importance of expanding research on this population and not restricting studies to children born extremely preterm with extremely low weight.…”
Section: Discussionmentioning
confidence: 96%
“…The authors found that the former only exhibited delays in fine motor skills, with no differences in gross motor skills, balance, body schema, spatial or temporal organization. Similarly, Ribeiro et al (38) compared the gross motor skills of premature and full-term children. The authors assessed 37 children aged between 5 and 6 years with a mean GA of 33.54 weeks in the preterm group.…”
Section: Discussionmentioning
confidence: 99%
“…The KTS test is widely used in Germany, and in other countries, by many healthcare professionals, being specially applied by physical educators [9,15]. In Brazil, the KTS test was validated by Gorla et al [14] and has been used to assess gross motor coordination in 5-14-year-old children [16,17].…”
Section: Methodsmentioning
confidence: 99%